2007
DOI: 10.1073/pnas.0702860104
|View full text |Cite
|
Sign up to set email alerts
|

Carotenoid silk coloration is controlled by a carotenoid-binding protein, a product of the Yellow blood gene

Abstract: Mechanisms for the uptake and transport of carotenoids, essential nutrients for humans, are not well understood in any animal system. The Y (Yellow blood) gene, a critical cocoon color determinant in the silkworm Bombyx mori, controls the uptake of carotenoids into the intestinal mucosa and the silk gland. Here we provide evidence that the Y gene corresponds to the intracellular carotenoid-binding protein (CBP) gene. In the Y recessive strain, the absence of an exon, likely due to an incorrect mRNA splicing ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
125
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 143 publications
(127 citation statements)
references
References 34 publications
2
125
0
Order By: Relevance
“…Nevertheless, we observed a barely detectable expression in the sch l mutant, resulting in the lethality of sch l at room temperature. Among B. mori mutants, TE-mediated gene disruption has also been reported for the Yellow blood and distinct translucent genes (42,43). In the revised B. mori genome datasets, Tc1-mariner type transposons and non-LTR retrotransposons comprise about 13.8 and 2.7% of the genome sequence, respectively (44).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, we observed a barely detectable expression in the sch l mutant, resulting in the lethality of sch l at room temperature. Among B. mori mutants, TE-mediated gene disruption has also been reported for the Yellow blood and distinct translucent genes (42,43). In the revised B. mori genome datasets, Tc1-mariner type transposons and non-LTR retrotransposons comprise about 13.8 and 2.7% of the genome sequence, respectively (44).…”
Section: Discussionmentioning
confidence: 99%
“…Yellow and pinkish colors are produced from carotenoids (4,7), and green colors are the products of flavonoids (8,9). Inheritance for the carotenoid cocoon has been well established and basically follows a classical Mendelian pattern (2,3,5,7). However, the inheritance pattern for the flavonoid cocoon is much more complicated and largely unknown (5).…”
mentioning
confidence: 99%
“…Silkworm cocoon colors are determined by two main pigments, carotenoids (4) and flavonoids (5), which are derived from mulberry leaves (6). Yellow and pinkish colors are produced from carotenoids (4,7), and green colors are the products of flavonoids (8,9). Inheritance for the carotenoid cocoon has been well established and basically follows a classical Mendelian pattern (2,3,5,7).…”
mentioning
confidence: 99%
“…A carotenoid binding protein (CBP) was isolated from the silk gland of the fifth instar Bombyx larvae [2]. CBP can be only found in Y gene dominant strains (Y/Y) with yellow cocoons rather than recessive strains (+ Y /+ Y ) with white cocoons [3][4][5][6]. RFLP analysis of the genes showed that CBP and the Y-gene were at the same chromosome locus and they may correspond to each other [7].…”
Section: Introductionmentioning
confidence: 99%
“…The domestic silkworm (Bombyx mori L.), an important economic species, is proposed as an animal model to elucidate this mechanism benefited from the research progress of carotenoid binding protein (CBP) [2,3] .…”
Section: Introductionmentioning
confidence: 99%